Sosialisasi Penyakit Diabetes Mellitus untuk Meningkatkan Pengetahuan Pasien - Prima Dewi; Ratna Wardani; Ferawati Ferawati (Lembaga Pengembangan Kinerja Dosen, 2025)
Diabetes mellitus (DM) is a non-communicable disease with a globally increasing prevalence, representing a major public health concern in the 21st century. This community service aimed to conduct a diabetes mellitus socialization program to enhance family members’ knowledge about the disease. Limited knowledge among the public often leads to delayed diagnosis, inadequate management, and higher risk of complications. A participatory approach and health education method were applied, emphasizing contextual, sustainable, evidence-based, and gender-sensitive principles. The program involved several stages, including stakeholder coordination, baseline surveys, needs assessment, development and delivery of training materials, and final evaluation. A total of 25 participants from families of diabetes patients at Dr. Sosodoro Djatikoesomo Bojonegoro Hospital took part in the program. Findings revealed that the intervention significantly improved participants’ knowledge, with an average score increase of 25.4 points or 52.7% from the pre-test (p < 0.001). Knowledge distribution shifted positively from a majority in the poor category (68%) to the fair-to-good category (92%). The greatest improvement was found in diabetes complications (36.4 points), followed by diabetes management (34.1 points), and diabetes symptoms (13.6 points). Participants’ satisfaction reached 100%, with 96% reporting being very satisfied. Interactive learning through discussion sessions proved effective in transferring knowledge and correcting misconceptions.